(3GdGbJUGO GdLRFj(B1 : s (3GdGbJUGO GdLRFj(B1 / s - (3dhRQj, fGOjIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2021)
(3GdGbJUGO h GdeTcdI GdGbJUGOjI , fXQjI GdWdH h GdYQV , bjGS GdeQhfGJ , JhGRf GdShb h JWHjbGJg , fXQjI GdeSJgdc , fXQjI GdefJL (B.s
(3eQGLY U(B. 129s
Keywords: (3GdGbJUGO GdLRFjs